Naturwissenschaft als Naturpoesie: Eine Stellungnahme Christoph Wilhelm Hufelands (1762–1832) gegen die naturphilosophische Medizin - Hansen, Werner (DMW - Deutsche Medizinische Wochenschrift, 2019)
At the turn to the 19th century, medicine in Germany became strongly influenced by the teachings of John Brown, who was a scottish physician. He had advocated a theory which regards and treats disorders as caused by defective or excessive excitation. His teachings were welcomed by natural philosophers like Schelling or Hegel. They modified it and integrated it into their systems of thinking. On the other hand Hufeland, who was one of the foremost physicians at that time, heavily opposed Brunonian System. This becomes evident in a fragmentary text that had been found only recently. In it he criticizes that these teachings were based on pure speculation and not on sound science as executed by Albrecht von Haller. It was meant ironically when he concluded that it thus resembled natural poetry. As viewed from today, evidence based medicine eventually established our modern ways for successfully diagnosing and treating disease. However, Hufelands disapproval appears to be still relevant. There are many people that even now advocate alternative ways and who consult quacks, healers etc.
Keywords: Brownianismus; Naturphilosophie; alternative Medizin; Christoph Wilhelm Hufeland; Albrecht von Haller